Determination of bacterial contamination in gutta-percha cones in a teaching dental clinic - Chang Prada, Alberto Andrés (2020)
Objective: The purpose of this study was to determinate the bacterial contamination of Beta (β) gutta-percha cones at 0, 24, 47 and 72 hours of the different supplies of the Universidad Científica del Sur, Lima 2020. Materials and Methods: 16 β-type gutta-percha cones were obtained of sealed packages under aseptic measurements, they were placed in vials with 2ml BHI and subsequently planted in BHI agar plates as well as in selective medias as Salted mannitol agar and MacConkey agar after 24 hours of incubation at 37 ° the plates were read and  count in CFU , the same procedure was performed for the other times evaluated 24, 48 and 72 hours, giving a total of 64 β-type gutta-percha cones. Results: It was observed that the level of bacterial contamination was the same among the different supplies in all the establish times of in this study 0, 24, 48 and 72 hours. Therefore, there were no significant differences in the level of bacterial contamination between the supplies. On the other hand, only statistically significant differences (p.044) were found between the different times of the supply number 5. Finally, all the samples submitted to the coagulase test had a negative result. Conclusion: The gutta-percha cones of type β were contaminated equally regardless of the supply in which they were stored or manipulated.